The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.22487/gravitasi.v21i2.15904
|View full text |Cite
|
Sign up to set email alerts
|

Review of ceramic materials and recent development of preparation methods

Abstract: Ceramics globally has been developed by various materials and methods to find suitable ceramics for specific applications. This paper discusses development of several methods in ceramic preparation such as hot-pressing, sintering, co-precipitation, and solid-state method. In 2001 up to 2019, hot-pressing method was used to manufacture ceramic B4C and SiAlCO as raw material doping by (W, Ti)C. In 2002 up to 2018 sintering method by using fly ash as raw material with an additional K2CO3, Na2CO3, and Nb2O5. In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The main reasons for this dispersion are the related mobile charge carriers as well as the polarized composition of the sample studied . The presence of several polarizations such as dipolar and ionic electronic polarizations as well as interfacial polarizations may be influenced by the large dielectric constant dispersions. ,,, By application of the local field, the electrons inside the material move opposite to the field by a small displacement (dipole moment) resulting in electronic polarization, and this behavior occurs above 1 GHz operating frequency . Moreover, the dielectric constant decreases with frequency (see Figure ); it is due to the permanent dipole moments which further affected the overall polarization mechanism inside the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reasons for this dispersion are the related mobile charge carriers as well as the polarized composition of the sample studied . The presence of several polarizations such as dipolar and ionic electronic polarizations as well as interfacial polarizations may be influenced by the large dielectric constant dispersions. ,,, By application of the local field, the electrons inside the material move opposite to the field by a small displacement (dipole moment) resulting in electronic polarization, and this behavior occurs above 1 GHz operating frequency . Moreover, the dielectric constant decreases with frequency (see Figure ); it is due to the permanent dipole moments which further affected the overall polarization mechanism inside the material.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, we previously systematically investigated the synthesis of Sr 3 Ti 2 O 7 bulk ceramics and obtained excellent microwave dielectric properties (ε r = 63, Q × f = 84,000 GHz, and τ f = 293 ppm/°C) . It has also been reported that compared to commercially available materials systems like CaTiO 3 -NdAlO 3 (ε r = 45, Q × f = 44,000 GHz, τ f = +3 ppm/°C) and CaLa 4 Ti 4 O 15 (ε r = 41.6, Q × f = 34,911 GHz, τ f = −25 ppm/°C), the Sr 3 Ti 2 O 7 ceramics show optimum microwave dielectric properties without noble elements. However, the large positive τ f value needs to be further optimized because it is unsuitable for real-world use. Colla et al concluded from a summary of structural parameters and microwave dielectric characteristics of complex perovskite ceramics based on Ba/Sr that the onset of octahedral tilting is the primary factor in determining the τ f values .…”
Section: Introductionmentioning
confidence: 95%